2014
DOI: 10.1017/s0305000914000695
|View full text |Cite
|
Sign up to set email alerts
|

Look at the gato! Code-switching in speech to toddlers

Abstract: We examined code-switching (CS) in the speech of twenty-four bilingual caregivers when speaking with their 18- to 24-month-old children. All parents CS at least once in a short play session, and some code-switched quite often (over 1/3 of utterances). This CS included both inter-sentential and intra-sentential switches, suggesting that at least some children are frequently exposed to mixed-language sentences. However, we found no evidence that this exposure to CS had any detrimental effect on children's word l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
110
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(126 citation statements)
references
References 39 publications
11
110
5
Order By: Relevance
“…Recently, Bail, Morini, and Newman (2015) found that 3%-4% of utterances heard by bilingual children in a laboratory play session contained within-sentence switches, which is consistent with earlier case studies that have estimated the proportion to be between 3% and 20% (Bentahila & Davies, 1995;Goodz, 1989;Nicoladis & Secco, 2000;Pan, 1995;Tare & Gelman, 2011). One unique challenge is the presence of mixed-language sentences, where two languages are used within a single utterance (e.g., Do you like the perro?…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Recently, Bail, Morini, and Newman (2015) found that 3%-4% of utterances heard by bilingual children in a laboratory play session contained within-sentence switches, which is consistent with earlier case studies that have estimated the proportion to be between 3% and 20% (Bentahila & Davies, 1995;Goodz, 1989;Nicoladis & Secco, 2000;Pan, 1995;Tare & Gelman, 2011). One unique challenge is the presence of mixed-language sentences, where two languages are used within a single utterance (e.g., Do you like the perro?…”
supporting
confidence: 74%
“…Previous studies using measures of parent report have suggested that language mixing affects children's vocabulary differently in different populations(Bail et al, 2015;Byers- Heinlein, 2013;Place & Hoff, 2016). However, when toddlers heard sentence frames in their non-dominant language, they successfully recognized target nouns in both languages.…”
mentioning
confidence: 89%
“…However, results of such offline and self-report studies are difficult to replicate (Paap & Sawi, 2014), and tend to differ from studies using online language measures. For example, Bail, Morini, and Newman (2014) found no effect of parental code switching measured in actual conversations on bilingual toddlers' language proficiency measures. Few studies have used online measures of bilingual speech perception or production to establish neural correlates of differences in mono-and bilingual language processing.…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, Bail et al. () found the opposite pattern, showing that intra‐sentential code‐switching was positively related to 18‐ to 24‐month‐old bilingual children's vocabulary size. Unlike Byers‐Heinlein (2013), Bail et al.…”
mentioning
confidence: 93%
“…Unlike Byers‐Heinlein (2013), Bail et al. () derived an objective measure of code‐switching, which they obtained from a parent–child interaction sample; their measure of productive vocabulary size was the same parent‐report measure used by Byers‐Heinlein (). How then to reconcile the rather conflicting findings across these studies?…”
mentioning
confidence: 99%